2020
DOI: 10.7554/elife.52160
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling in cochlear supporting cells reduces hair cell excitability by increasing the extracellular space

Abstract: Neurons in developing sensory pathways exhibit spontaneous bursts of electrical activity that are critical for survival, maturation and circuit refinement. In the auditory system, intrinsically generated activity arises within the cochlea, but the molecular mechanisms that initiate this activity remain poorly understood. We show that burst firing of mouse inner hair cells prior to hearing onset requires P2RY1 autoreceptors expressed by inner supporting cells. P2RY1 activation triggers K+ efflux and depolarizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 68 publications
7
79
1
Order By: Relevance
“…Only the dorsal parts of the IC, including DCIC and LCIC, are accessible for calcium imaging (Babola et al, 2018, Wong andBorst, 2019). Consistent with previous reports (Babola et al, 2018, Babola et al, 2020, typical spontaneous calcium transients in the dorsal surface of the IC appear as stationary and discrete events that (1) have a relatively homogeneous intensity profile along their major axis, (2) show confined spread along the future tonotopic axis that is approximately perpendicular to the major axis ( Figures 1C and Supplementary Figure 1B, major axes labeled as magenta arrows), and (3) appear as a single band in the most medial part or dual bands in more lateral parts of the IC (See also Movie S1). We refer to these calcium transients as "spontaneous bands" or "spontaneous events".…”
Section: Evolving Spatiotemporal Properties Of Spontaneous Activity Asupporting
confidence: 85%
See 2 more Smart Citations
“…Only the dorsal parts of the IC, including DCIC and LCIC, are accessible for calcium imaging (Babola et al, 2018, Wong andBorst, 2019). Consistent with previous reports (Babola et al, 2018, Babola et al, 2020, typical spontaneous calcium transients in the dorsal surface of the IC appear as stationary and discrete events that (1) have a relatively homogeneous intensity profile along their major axis, (2) show confined spread along the future tonotopic axis that is approximately perpendicular to the major axis ( Figures 1C and Supplementary Figure 1B, major axes labeled as magenta arrows), and (3) appear as a single band in the most medial part or dual bands in more lateral parts of the IC (See also Movie S1). We refer to these calcium transients as "spontaneous bands" or "spontaneous events".…”
Section: Evolving Spatiotemporal Properties Of Spontaneous Activity Asupporting
confidence: 85%
“…In the cochleae, groups of inner hair cells (IHC) fire bursts of action potentials that propagate to central auditory nuclei via ascending pathways to coordinate activity throughout the auditory system prior to hearing onset (Tritsch et al, 2007. Although central auditory activity may inherit many properties directly from the periphery, it manifests with distinct patterns and novel features (Babola et al, 2018, Sun et al, 2018, Babola et al, 2020. Consequently, understanding the characteristics of spontaneous activity in the central auditory system may provide insight into the maturation of circuit connectivity and the development of higher-order auditory functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing mammalian cochlea, supporting cells within Kölliker's organ spontaneously release ATP, initiating a purinergic signaling cascade that releases Ca 2+ from intracellular stores and activates TMEM16A, a Ca 2+ -activated Clchannel (Wang et al, 2015;Babola et al, 2020). Efflux of Clions draws positive K + ions into the extracellular space, producing a temporary osmotic gradient that draws water into the extracellular space.…”
Section: Spontaneous Electrical Activity Of Inner Supporting Cells Emmentioning
confidence: 99%
“…Prior to hearing onset, a group of glial-like inner supporting cells (ISCs) located adjacent to inner hair cells (IHCs) spontaneously release ATP, activating a metabotropic purinergic cascade that ultimately results in release of K + , IHC depolarization and subsequent burst firing of spiral ganglion (SGNs) and central auditory neurons (Sonntag et al, 2009;Babola et al, 2018). Recent mechanistic studies revealed that activation of purinergic P2Y1 receptors and downstream gating of Ca 2+ -activated chloride channels (TMEM16A) are required, and that correlated activity in central auditory circuits is sensitive to P2RY1 inhibition in vivo after the first postnatal week (Wang et al, 2015;Babola et al, 2020). Efferent inhibition of IHCs through activation of α9 subunit-containing nicotinic acetylcholine receptors has also been implicated in both initiating (Johnson et al, 2012) and modulating (Clause et al, 2014) spontaneous activity during this period.…”
Section: Introductionmentioning
confidence: 99%